Authors review on drug nanocrystals: A progress to targeted delivery - Kumar M.; Shanthi N.; Rajnikanth P.S.; Mahato A.K. (My University, 2025)
In the last few decades, researchers and pharmaceutical industries have been developing new approaches to overcome the solubility and bioavailability limits observed with poorly soluble drugs. With the advancement of nanotechnology, nanocrystals have emerged as a great potential to overcome these limitations. Nanocrystals owing to its ability to modify the physicochemical and biological properties of the drug have gained wide-spread attention among the research scientists. This review provides comprehensive detail on the associated advantages, challenges, factors affecting physicochemical properties, and optimization parameters about the stability of nanocrystals. In this review, the evolu-tion of nanocrystals is discussed as first-generation simple nanocrystals, second-generation nanocrystals within a carrier, and third-generation surface-modified nanocrys-tals. It also provides a detailed account of various preparation methods and evaluation of surface-modified nanocrystals. In the proposed "King Design," nanocrystals of the third generation are placed on the top due to their advantage over other nanocarriers like high drug payload, site-specific delivery, improved activity, commercial manufacturing, and easy scale-up. Third generations nanocrystals can provide a novel therapeutic solution for the site-specific, targeted, and efficient delivery for treatment of various acute as well as chronic diseases with high stability and scale-up potential. © 2020 Bentham Science Publishers.